012. A 7 Years Old Girl With Congenital Pseudoarthosis of Tibia : An Extremely Rare Case, A Case Report - Fatrahady, Lalu Shaktisila; Purnaning, Dyah (JBN (Jurnal Bedah Nasional), 2024)
Background : Congenital pseudoarthosis of tibia is a an extremely rare condition. The incidence ranges from 1:140,000-190,000. Risk Factors Up to 55% associated with Neurofibromatosis Type 1 and 15% associated with Fibrous Dysplasia. It is mostly found in 50-55% of patients with anterolateral bowing and only 6-10% of patients with neurofibromatosis will have anterolateral tibial bowing. The Association with neurofibromatosis stigmata including skin and osseous lesions. It is also usually associated with a dysplastic segment of bone, which undergoes fracture after a trivial trauma or spontaneously.   Case : This is a case report of a 7 year old girl, who presented with progressive deformity of right leg. She was diagnosed with congenital pseudoarthosis tibia and had fracture 12 months  before ago. The patient was has undergone treatment with ORIF Plate Screw and had undergone removal implant 3 months after ORIF. After removal implant patient complained agulation at the site of the fracture and it was getting worse by time. Several choice of treatment with multiple osteotomies, bone grafting, intramedullary nailing and stabilization with ilizarao external fixator followed by cast immobilization. Conclusion: This patient was treated with multiple osteotomies following with intramedullary nailing. On follow up deformity was corrected and union was achieved.